2021
DOI: 10.1002/ana.26019
|View full text |Cite
|
Sign up to set email alerts
|

MED27 Variants Cause Developmental Delay, Dystonia, and Cerebellar Hypoplasia

Abstract: The Mediator multiprotein complex functions as a regulator of RNA polymerase II–catalyzed gene transcription. In this study, exome sequencing detected biallelic putative disease‐causing variants in MED27, encoding Mediator complex subunit 27, in 16 patients from 11 families with a novel neurodevelopmental syndrome. Patient phenotypes are highly homogeneous, including global developmental delay, intellectual disability, axial hypotonia with distal spasticity, dystonic movements, and cerebellar hypoplasia. Seizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…Both SLC6 transportopathies and inherited disorders of GPI deficiency are associated with a broad range of neurological diseases. 26,27 Early neuroimaging abnormalities in our patients are similar to those described in MED27-related disease 6 and GPI deficiency disorders with cerebellar defects and white matter changes. 27 To date, the later imaging findings in the older sibling have not been reported in MED27 disease.…”
Section: Discussionsupporting
confidence: 75%
“…Both SLC6 transportopathies and inherited disorders of GPI deficiency are associated with a broad range of neurological diseases. 26,27 Early neuroimaging abnormalities in our patients are similar to those described in MED27-related disease 6 and GPI deficiency disorders with cerebellar defects and white matter changes. 27 To date, the later imaging findings in the older sibling have not been reported in MED27 disease.…”
Section: Discussionsupporting
confidence: 75%
“…Among these genes, 14 were found to have variants in two or more families (AMPD2 [2; MIM: 102771], AP3B2 [2; MIM: 602166], CLP1 [4; MIM: 608757], DDC [2; MIM: 107930], FOXG1 [2; MIM: 164874], GRM7 [2; MIM: 604101], LAMA1 [2; MIM: 150320], LARP7 [2; MIM: 612026], LPAR6 [2; MIM: 609239], PARD3B [2; MIM: 619353], 52 RNASEH2A [2; MIM: 606034], SNX14 [2; MIM: 616105], TBC1D23 [2; MIM: 617687], and WDR81 [2; MIM: 614218]). Placing these findings in the larger context of our full NDD cohort, which includes TBM1, 13 TBM2, and several additional case and cohort reports, [53][54][55][56][57][58][59][60][61][62][63] there are 185 known NDD-associated genes that contribute to a total of 218 molecular diagnoses.…”
Section: Known Ndd-associated Genesmentioning
confidence: 87%
“…It is located in the junction of the Head and Tail of the MED complex ( Figure 3 ) and interacts with MED29, which in turn interacts with MED14 to link the Tail module with the Head and Middle modules ( Figure 3 ). Though the specific biological functions of MED27 are unknown yet, it clearly plays an essential role in early embryonic and neuronal development [ 80 , 81 ]. MED27 has been found that is highly expressed in BC tissues and cells and its expression correlates with tumor size and grade and the high expression of MED27 had a poor prognosis [ 82 ].…”
Section: Mediator and Breast Cancermentioning
confidence: 99%